PENERAPAN PASAL 378 KITAB UNDANG-UNDANG HUKUM PIDANA DALAM PENERBITAN BILYET GIRO KOSONG (STUDI KASUS PUTUSAN NOMOR 291/PID.B/2014/PN.YYK) - Deby Mardina; Riswadi (Fakultas Hukum Universitas Borobudur, 2022)
Bilyet giro is a new type of securities compared to other securities by demand, is a book transfer order that functions as a means of payment. However, in practice there is often a fraud against the bilyet giro, which is often known as an empty bilyet giro, resulting in payment failures. the formulation of the problem in this study, is the application of Article 378 of the Criminal Code in Decision No. 291/Pid.B/2014/PN.Yyk. is in accordance with the applicable legal provisions, and what is the basis for the judge's consideration in making decisions against perpetrators of criminal acts of fraud that to be able to prove that the defendant is proven not guilty of committing a criminal act of fraud, where there must be elements in Article 378 of the Criminal Code for the crime of fraud, elements with the intention of benefiting oneself or another person against the law. While the basis for the judge's consideration in making a decision against the perpetrators of the crime of fraud in Decision No. 291/Pid.B/2014/PN.Yyk. stated that the defendant was proven to have committed the act as charged to him, but the act was not a criminal act as regulated in Article 378 of the Criminal Code. On the basis of the description of the elements of a criminal offense in the indictment, the Yogyakarta District Court rendered a decision free from all lawsuits against the defendant, the decision was given because the defendant was proven guilty after the examination process in court, but the act was not a criminal act as stipulated in Article 191 paragraph (2) Criminal Procedure Code.